PD-1 inhibitors-based second-line therapy for metastatic gastric cancer - Gou, Miaomiao; Zhang, Yong; Wang, Zhikuan; Dai, Guanghai (Frontiers in Immunology, 2023)
Background Metastatic gastric cancer (MGC) patients with progression on first-line treatment still have poor outcomes on chemotherapy. The KEYNOTE-061 study demonstrated that pembrolizumab, a PD-1inhibitor, was not better than paclitaxel as second-line therapy for MGC. Herein, we explored the efficacy and safety of PD-1inhibitor based treatment for MGC patients in the second line. Methods In this observational, retrospective study, we enrolled MGC patients treated with anti-PD-1 based therapy as second-line in our hospital. We primarily assessed the treatment’s efficacy and safety. We also evaluated the relationship between clinical features and outcomes using univariate and multivariate analyses. Results We enrolled 129 patients with an objective response rate (ORR) of 16.3% and a disease control rate (DCR) of 79.1%. Patients treated with PD-1inhibitor combined with chemotherapy and anti-angiogenic agents had ORR of 19.6% and higher DCR of 94.1%. The median progression-free survival (PFS) was 4.10 months, and the median overall survival (OS) was 7.60 months. In univariate analysis, patients treated with PD-1inhibitor combined with chemotherapy and anti-angiogenic agents and with prior anti-PD-1 history were significantly associated with favorable PFS and OS. In the multivariate analysis, different combination therapy and prior anti-PD-1 history were independent prognosis biomarkers for PFS and OS. Grade 3 or 4 treatment-related adverse events (TRAEs) occurred in 28 (21.7%) patients. Common adverse events (AEs) included fatigue, hyper/hypothyroidism, neutrophil decrease, anemia, skin reactions, proteinuria, and hypertension. We did not observe treatment-related deaths. Conclusion Our current results indicated that PD-1-inhibitor and chemo-anti-angiogenic agents combination therapy and prior PD-1 treatment history might improve clinical activity for GC immunotherapy as second-line treatment with acceptable safety profiles. Further studies are needed to verify those outcomes for MGC in other centers.